Hematologic parameters as the predictors for metabolic syndrome in perimenopausal and postmenopausal women living in urban area: a preliminary report - Vichinsartvichai, Patsama; Sirirat, Siriwan (Menopause Review/Przegląd Menopauzalny, 2016)
Introduction : Prevalence of metabolic syndrome increases drastically during menopausal transition. Chronic inflammation is proposed as the basic pathophysiology of metabolic syndrome (MetS). Aim of the study: To compare mean white blood cell count between perimenopausal and postmenopausal women with and without MetS and find the prevalence of MetS in this patient group. Material and methods: A total of 140 healthy perimenopausal and postmenopausal women were interviewed and underwent anthropometric measurements, biochemical investigations for MetS and hematologic parameters. MetS was defined according to the Joint Interim Statement 2009 criteria. The outcome measures were the hematologic parameters between women with and without MetS, correlation of hematologic parameters with MetS components and optimum cutoff for MetS prediction. Results: The mean age of participants was 50 years. 63.6% were perimenopausal and 36.4% were postmenopausal ones. The prevalence of MetS was 21.4% (95% CI: 15.0-27.9). The women with MetS had a significantly higher level of white blood cell (WBC) counts (7,466.7 and 6,514.6; p = 0.006) and total lymphocyte counts (2,572.0 and 2,207.7; p = 0.003). The optimum cutoff of WBC counts and total lymphocyte counts for prediction of metabolic syndrome was 6,750 cells/ml (sensitivity = 0.633; specificity = 0.591, p = 0.019) and 2,232 cells/ml (sensitivity = 0.667; specificity = 0.518, p = 0.016), respectively. Conclusion : White blood cell and total lymphocyte counts were higher in perimenopausal and postmenopausal women with MetS. However, both hematologic parameters were poor predictors for MetS in peri- and postmenopausal women.